Erythrocytosis in hepatocellular carcinoma portends poor prognosis by respiratory dysfunction secondary to mitochondrial DNA mutations. Issue 1 (25th November 2016) - Ke, Shizhong; Chen, Shuzhen; Dong, Zihui; Hong, Christopher S.; Zhang, Qi; Tang, Liang; Yang, Pinghua; Zhai, Jian; Yan, Hexin; Shen, Feng; Zhuang, Zhengping; Wen, Wen; et al.
Abstract : Erythrocytosis is a common paraneoplastic syndrome associated with hepatocellular carcinoma. Although increased erythropoietin (EPO) is found in these patients, the clinical significance and molecular mechanisms underlying this observation are unclear. We demonstrate an inverse relationship between EPO production and overall prognosis in our cohort of 664 patients as well as in data from The Cancer Genome Atlas. In the subset of hepatocellular carcinoma patients with erythrocytosis, we identified somatic mutations of mitochondrial DNA, resulting in impairment of respiratory metabolism, which sequentially led to depletion of α‐ketoglutarate, stabilization of hypoxia inducible factor‐α, and expression of target genes such as EPO. Cell lines and patient‐derived xenograft models were used to demonstrate that EPO promoted cancer stem cell self‐renewal and expansion in an autocrine/paracrine manner through enhanced Janus kinase/signal transducer and activator of transcription signaling both in vitro and in vivo . Furthermore, to explore the therapeutic targeting of EPO‐induced tumor changes, we found that blocking EPO signaling with soluble EPO receptor extracellular domain Fc fusion protein could inhibit tumor growth both in vitro and in vivo . Conclusion: These findings suggest clinical and therapeutic implications for erythrocytosis in hepatocellular carcinoma. There is an underlying link between mitochondrial function and hypoxia inducible factor alpha signaling, revealing a mechanism of erythrocytosis in a subset of hepatocellular carcinoma patients who may benefit from treatment involving EPO signaling interference. (Hepatology 2017;65:134‐151).